Firm Ownership and Enterprise Risk Management: Evidence from a Developing Country - Chee Keong, Ooi; Adamu Pantamee, Abdurrahman; Mohamad, Shafi; Wing Chong Garrett, Kwong (International Journal of Psychosocial Rehabilitation, 2020)
This study examines the association between the ownership structure and enterprise risk management. The findings of the current study show that enterprise risk management is significantly influenced by ownership structure. This study used secondary data of 200 Malaysian firms listed on the Malaysian Stock Exchange (Bursa Malaysia) during the period 2014 to 2018. We use dispersed ownership concentration and managerial ownership concentration as the proxy of ownership structure and correlate with the adoption of enterprise risk management. Our results are consistent with our hypothesis, as we found a positive and significant relationship between enterprise risk management and ownership structure. Moreover, the results are consistent with the hypothesis that there is a positive relationship of dispersed ownership structure with the adoption of enterprise risk management and a negative relationship of managerial ownership with the adoption of enterprise risk management.